2013
DOI: 10.1183/09031936.00038713
|View full text |Cite
|
Sign up to set email alerts
|

Why inflammatory phenotyping is necessary for successful drug evaluation in asthma and COPD

Abstract: @ERSpublicationsPathway specific drug trials must account for prevalence of the pathway by subject selection or by adjusting sample size http://ow.ly/nx4k9Identifying and treating the eosinophilic subtype of asthma has now achieved renewed importance for clinicians and scientists involved in clinical trials. This has happened following the near-demise of an antiinterleukin (IL)-5 monoclonal antibody (mepolizumab) as a candidate for asthma treatment [1] and its resurrection in trials based around using induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
1
5
1
Order By: Relevance
“…In addition it was reassuring that the patients for whom the clinician did not feel the need to prescribe an ICS after their asthma clinic visit, did not report any exacerbation in the following year. This suggests that using the mere cell count to assess inflammation in clinical practice may still carry some value and help phenotype asthma patients [9]. This assumption was indeed further supported by the DREAM study results where the efficacy of mepolizumab was partly dependent on the blood eosinophil count [10].…”
Section: From the Authorssupporting
confidence: 68%
“…In addition it was reassuring that the patients for whom the clinician did not feel the need to prescribe an ICS after their asthma clinic visit, did not report any exacerbation in the following year. This suggests that using the mere cell count to assess inflammation in clinical practice may still carry some value and help phenotype asthma patients [9]. This assumption was indeed further supported by the DREAM study results where the efficacy of mepolizumab was partly dependent on the blood eosinophil count [10].…”
Section: From the Authorssupporting
confidence: 68%
“… 24–26 Earlier work focused on sputum eosinophils, but blood eosinophils are now being accepted as an alternative measurement that is more practical to use in a clinical setting. 27 28 The clinical relevance of the 2.4% cut-off in blood eosinophil levels requires additional exploration; however, it lies between the 3% value commonly used to define sputum eosinophilia 8 22 29 and the 2% value that was identified as a relevant cut-off point in patients with COPD based on an analysis of the Evaluation of COPD Longitudinally to Identify Predictive Surrogate End points (ECLIPSE) cohort. 30 No minimal clinically important difference has yet been defined for eosinophilia in COPD, 29 but clinically meaningful differences have been found in other studies and analyses based on either a 2% or 2.5% cut-off.…”
Section: Discussionmentioning
confidence: 99%
“… 27 28 The clinical relevance of the 2.4% cut-off in blood eosinophil levels requires additional exploration; however, it lies between the 3% value commonly used to define sputum eosinophilia 8 22 29 and the 2% value that was identified as a relevant cut-off point in patients with COPD based on an analysis of the Evaluation of COPD Longitudinally to Identify Predictive Surrogate End points (ECLIPSE) cohort. 30 No minimal clinically important difference has yet been defined for eosinophilia in COPD, 29 but clinically meaningful differences have been found in other studies and analyses based on either a 2% or 2.5% cut-off. 3 16 20 23 In particular, this work complements the post hoc subgroup analysis of the same clinical trials of FF/VI versus VI that was conducted by Pascoe et al 23 That analysis found that patients with COPD with blood eosinophils ≥2% at baseline experienced a reduction in exacerbation rates of 29% (p<0.001) when treated with FF/VI (all strengths) versus VI alone; the corresponding reduction in patients with eosinophils <2% was 10% (p=0.283).…”
Section: Discussionmentioning
confidence: 99%
“…Our approach was therefore different from that used in hierarchical unsupervised cluster analysis. We do not deny the great interest of this type of cluster analysis in the emergence of clinical asthma phenotypes, but we believe that classifying asthmatics according to their eosinophilic profile is useful because sputum and blood eosinophils are good biomarkers to target treatment and predict response to corticoids or biologicals directed towards Th2 cytokines [37,38]. Furthermore, it has recently been advocated that sputum eosinophils may be a valuable outcome in asthma drug trials [37].…”
Section: Discussionmentioning
confidence: 99%